Imperfect streetscapes. Design climate-adaptive nature-based urban regeneration - Alessandro Raffa (Anuari d’Arquitectura i Societat)
Imperfection, uncertainty and adaptation are intrinsically intertwined concepts that reflect the complex nature of human existence in the Anthropocene. This contribution delves into the nexus of imperfection, uncertainty, and adaptation through the lens of Green Urban Regeneration, focusing on the transformation of mono-functional infrastructural spaces into Climate-Adaptive Nature-based Streetscapes. Cities, endeavoring to adjust to the shifting and uncertain climate patterns, are already embracing imperfection in the regenerative design of Streetscapes, turning them into hybrid, multi-purpose, inclusive and Nature-based streetscapes. As part of an ongoing EU-funded research, this contribution explores how embracing imperfection can inform the conceptual and operational framework for innovative Climate-Adaptive Nature-based Streetscape Regenerative Design.